Suppression of Mcl‐1 induces apoptosis in mouse peritoneal macrophages infected with Mycobacterium tuberculosis. (15th April 2016) - Wang, Fei‐yu; Wang, Xin‐min; Wang, Chan; Wang, Xiao‐fang; Zhang, Yu‐qing; Wu, Jiang‐dong; Wu, Fang; Zhang, Wan‐jiang; Zhang, Le
ABSTRACT: The effect of myeloid cell leukemia‐1 (Mcl‐1) inhibition on apoptosis of peritoneal macrophages in mice infected with Mycobacterium tuberculosis was investigated and the primary signaling pathway associated with the transcriptional regulation of Mcl‐1 was identified. Real‐time PCR and western blotting indicated that Mcl‐1 transcript and protein expression are upregulated during infection with virulent M. tuberculosis H37Rv and Xinjiang strains but not with attenuated M. tuberculosis strain H37Ra or Bacillus Calmette–Guérin. Mcl‐1 transcript and protein expression were downregulated by specific inhibitors of the Janus kinase/signal transducer and activator of transcription (JAK/STAT), mitogen‐activated protein kinase (MAPK) and phosphoinositol 3‐kinase (PI3K) pathways (AG490, PD98059 and LY294002, respectively). The strongest inhibitor of Mcl‐1 expression was PD98059, the MAPK inhibitor. Flow cytometry demonstrated that the rate of apoptosis in peritoneal macrophages is significantly higher in mice infected with M. tuberculosis and the rate of apoptosis is correlated with the virulence of the strain of M. tuberculosis . Apoptosis was found to be upregulated by AG490, PD98059 and LY294002, whereas inhibition of the MAPK pathway sensitized the infected macrophages to apoptosis. Taken together, these results suggest that specific downregulation of Mcl‐1 significantly increases apoptosis of peritoneal macrophages and that the MAPK signaling pathway is the primary mediator of Mcl‐1 expression.